Elementos claves para el uso eficiente de los recursos agropecuarios en Providencia (Colombia) Proyecto “Cosechando agua, asegurando futuro” - Jaime Fabian Cruz; Juan Daniel Valderrama; Oswan Mora (Universidad Antonio Nariño, 2024)
This book is a tool for the entire community of Providencia, helping to highlight the need for better use of water resources, soil, and energy, with the aim of developing better agricultural and livestock practices with minimal environmental impact. Efficient use of water resources and organic waste are some of the strategies implemented on their model farms to be replicated throughout the island community